Better Students Ask More Questions.
2 Answers | add yours
High School Teacher
To solve this equation: 3t(t+2)=1 first rearrange:
`therefore 3t(t+2)=1` becomes `3t^2+6t-1=0`
It cannot be factored normally so use the quadratic formula:
`x=(-b+-sqrt(b^2-4ac))/(2a)` where a=3, b=6 and c=-1
`therefore x=(-6+-sqrt(36-4(3)(-1)))/(2(3))` Care with negative symbols
`therefore x=0.1547` or `x=- 2.1547`
Ans: x=0.1547 or x=- 2.1547
Posted by durbanville on August 26, 2013 at 7:39 PM (Answer #1)
eNoter, TA, Mathematician, Super Tutor, Tutor
3t(t+2)=1 first you use the distributive property 3t x everything inside the parenthesis you will end up with:
`3t^2+6t=1` then move the 1 by taking it out on both sides. you will end up with:
`3t^2+6t-1=0` the next step is to use the quadratic formula.
`-6+-sqrt(6^2-4(3)(-1))` over 6 then simplify the problem:
`-6+-sqrt(36+12)` divided by 6
`-6+-sqrt(48)` divided by 6
x= .153 x=-2.153
Posted by atyourservice on February 12, 2014 at 6:05 PM (Answer #2)
Join to answer this question
Join a community of thousands of dedicated teachers and students.